2022
DOI: 10.1159/000522318
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Outcome Measures for Preterm and Hospitalized Neonates: An ICHOM Standard Set

Abstract: <b><i>Introduction:</i></b> Approximately, one in ten infants is born preterm or requires hospitalization at birth. These complications at birth have long-term consequences that can extend into childhood and adulthood. Timely detection of developmental delay through surveillance could enable tailored support for these babies and their families. However, the possibilities for follow-up are limited, especially in middle- and low-income countries, and the tools to do so are either not avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Investment in eliciting and supporting family values, needs and preferences is required 12,26,29 . On a general level, it is necessary to work together to define commonly used outcome parameters for extreme prematurity so that they provide a better reflection of what matters to physicians, premature infants and their families, in terms of both research and counselling 25,30 . Recent initiatives have been hopeful and may help to personalise prenatal counselling and decision‐making and communicate individual values 25,26,30 …”
Section: Discussionmentioning
confidence: 99%
“…Investment in eliciting and supporting family values, needs and preferences is required 12,26,29 . On a general level, it is necessary to work together to define commonly used outcome parameters for extreme prematurity so that they provide a better reflection of what matters to physicians, premature infants and their families, in terms of both research and counselling 25,30 . Recent initiatives have been hopeful and may help to personalise prenatal counselling and decision‐making and communicate individual values 25,26,30 …”
Section: Discussionmentioning
confidence: 99%
“…The use of tools specifically designed for patients with liver cirrhosis may hence be key to achieve good results. Numerous studies have shown that it is essential to use tools specific to the patient's specific pathology, as has been seen in several chronic pathologies [45][46][47].…”
Section: Discussionmentioning
confidence: 99%